Measuring Venezuelan emigration with Twitter - Ricardo Hausmann; Julian Hinz; Muhammed A. Yildirim (Kiel Institute for the World Economy (IfW), 2018)
Venezuela has seen an unprecedented exodus of people in recent months. In response to a dramatic economic downturn in which inflation is soaring, oil production tanking, and a humanitarian catastrophe unfolding, many Venezuelans are seeking refuge in neighboring countries. However, the lack of official numbers on emigration from the Venezuelan government, and receiving countries largely refusing to acknowledge a refugee status for affected people, it has been difficult to quantify the magnitude of this crisis. In this note we document how we use data from the social media service Twitter to measure the emigration of people from Venezuela. Using a simple statistical model that allows us to correct for a sampling bias in the data, we estimate that up to 2,9 million Venezuelans have left the country in the past year.
Keywords: F22; C55; 330; migration; social media